Cognitive Decline Complaints Scale (CDCS) - Frias, Joana Rita Lopes (2022)
Subjective Cognitive Complaints (SCC), which result from the self-perception of Subjective Cognitive Decline (SCD), are frequently reported by older adult people. The Cognitive Decline Complaints Scale (CDCS) assesses subjective complaints of cognitive decline in several cognitive domains - attention and concentration, memory, language, executive functions, temporal and spatial orientation and visuospatial function - through three levels of severity. This study aims to psychometrically validate this instrument considering the Classical Test Theory, and to establish preliminary normative data of the CDCS for the elderly Portuguese population. The communitybased sample consisted of 199 cognitively healthy Portuguese adults and older adults, stratified according to several sociodemographic variables with a distribution similar to that observed in the Portuguese population. All participants responded, in addition to the CDCS, to an extensive neuropsychological assessment protocol. The psychometric characteristics of the CDCS were generally adequate for this community sample. As for the sociodemographic variables analyzed, only the geographic region had differences in the CDCS scores, which can be explained by differences observed in the levels of depressive symptoms between the mainland and the island of Portugal (Açores). There were no significant correlations or differences between the CDCS scores and age and educational level and, therefore normative data were explored considering the total sample. The CDCS is a scale that allows the detailed assessment of subjective cognitive complaints and the determination of whether or not such complaints are considered normative, which will facilitate an empirically based understanding of this dimension of psychological functioning and also provide indications as to the need for a more extensive neuropsychological assessment.